2018
DOI: 10.1093/geronb/gbx160
|View full text |Cite
|
Sign up to set email alerts
|

Taking the Biggest First: Age Differences in Preferences for Monetary and Hedonic Sequences

Abstract: We discuss "taking the biggest first" preferences in light of prior mixed findings on age differences in sequence preferences. We highlight the distinct roles of experience- and emotion-based decision-making processes. We propose applications to financial and health-care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 48 publications
5
21
0
Order By: Relevance
“…Although older adults face well‐documented age‐related decline in cognitive abilities that could harm their ability to make financial decisions (Gamble, Boyle, Yu, & Bennett, ), it has been suggested that they also have more experience‐based knowledge that could benefit financial decisions (Bruine de Bruin et al, ; Bruine de Bruin, Parker, & Fischhoff, ; Kovalchik, Camerer, Grether, Plott, & Allman, ; Li, Baldassi, Johnson, & Weber, ; Li et al, ). Additionally, older adults may experience changes in emotions and motivation, which could be relevant to making decisions (e.g., Bruine de Bruin, ; Strough, Bruine de Bruin, & Parker, in press; Strough, Parker, & Bruine de Bruin, ). Our paper is part of an emerging literature that aims to understand age differences in decision making, roles of various cognitive individual‐differences characteristics (such as numeracy and experience‐based knowledge), and noncognitive individual‐differences characteristics (such as negative emotions and motivation).…”
Section: Introductionmentioning
confidence: 99%
“…Although older adults face well‐documented age‐related decline in cognitive abilities that could harm their ability to make financial decisions (Gamble, Boyle, Yu, & Bennett, ), it has been suggested that they also have more experience‐based knowledge that could benefit financial decisions (Bruine de Bruin et al, ; Bruine de Bruin, Parker, & Fischhoff, ; Kovalchik, Camerer, Grether, Plott, & Allman, ; Li, Baldassi, Johnson, & Weber, ; Li et al, ). Additionally, older adults may experience changes in emotions and motivation, which could be relevant to making decisions (e.g., Bruine de Bruin, ; Strough, Bruine de Bruin, & Parker, in press; Strough, Parker, & Bruine de Bruin, ). Our paper is part of an emerging literature that aims to understand age differences in decision making, roles of various cognitive individual‐differences characteristics (such as numeracy and experience‐based knowledge), and noncognitive individual‐differences characteristics (such as negative emotions and motivation).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Strough et al (2019) found that older adults preferred taking the biggest event sooner instead of later, in both monetary and hedonic contexts. Löckenhoff and Samanez-Larkin (2020) also found greater preference for decreasing sequences (of monetary outcomes) among older age subjects.…”
Section: Theoretical Frameworkmentioning
confidence: 86%
“…Finally, we expect that the relative inattention to duration and the desire for good endings are part of people’s basic cognitive machinery and as such are not greatly modified by experience or education (but see Strough et al, 2019 ). Nevertheless, there is research showing (a) that marketers are likely to target behavioral biases, particularly of people who are poor and have less education, and (b) that individuals learn from experience with various financial products.…”
Section: Hedonics Of Debt Paymentmentioning
confidence: 99%